Analysis of the Effect Of Price, Place and Service Quality On Customer Satisfaction at Apek Motor Sidoarjo - Rochmat Bahauddin; Hadi Purnomo (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study aims to determine the effect of price (X1), place (X2) and service quality (X3) on customer satisfaction (Y) at Apek Motor Sidoarjo workshop, this study uses quantitative methods, the population in this study are all customers of Apek Motor Sidoarjo workshop. the sample in this study amounted to 100 people. With multiple linear regression analysis method. The results of this study indicate that 1) The price variable has a partial effect on customer satisfaction 2) The place variable has a partial effect on customer satisfaction 3) The service quality variable has a partial effect on customer satisfaction, 4) Price, place, and service quality simultaneously affect customer satisfaction